2021
DOI: 10.3390/jcm10225418
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine C-C Motif Ligand 7 (CCL7), a Biomarker of Atherosclerosis, Is Associated with the Severity of Alopecia Areata: A Preliminary Study

Abstract: Alopecia areata is an autoimmune, inflammatory form of non-scarring hair loss that may affect any hair-bearing area. Recently, an increased risk of cardiovascular disorders has been described in patients with alopecia areata. The aim of the study was to evaluate the serum concentrations of proinflammatory proteins associated with atherosclerosis (chemokine C-C motif ligand 4; CCL4, chemokine C-C motif ligand 7, CCL7; and sortilin, SORT1), and cardiovascular risk (myeloperoxidase, MPO; interleukin 1 receptor-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“… 35 Elevated levels of CCL7 are present in laparoscopic aspiration samples from adults with endometriosis, 36 and uterine CCL7 production has been associated with leukocyte chemotaxis in cervical ripening, 37 and with preterm delivery. 38 Serum and plasma levels of CCL7 have been proposed as biomarkers of atherosclerosis, 39 systemic sclerosis, 40 and severity of COVID‐19 infection. 41 Elevated plasma levels of both TGF‐β and CCL7 have also been associated with amnestic mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Elevated levels of CCL7 are present in laparoscopic aspiration samples from adults with endometriosis, 36 and uterine CCL7 production has been associated with leukocyte chemotaxis in cervical ripening, 37 and with preterm delivery. 38 Serum and plasma levels of CCL7 have been proposed as biomarkers of atherosclerosis, 39 systemic sclerosis, 40 and severity of COVID‐19 infection. 41 Elevated plasma levels of both TGF‐β and CCL7 have also been associated with amnestic mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…43 Another study investigating the connection between atherosclerosis and AA found that when evaluating the serum concentrations of proinflammatory proteins, particularly CCL7, there was a positive correlation between the serum concentration of CCL7 and the severity of AA (r = 0.281; p = 0.03), suggesting that the severity of AA may be associated with an increased risk of atherosclerosis. 55 Another study with 89 patients with AA found significantly higher plasma levels of cardiac troponin I (cTnI) and CRP in patients with AA compared to patients with AGA and controls without hair loss. 56 They also found that AA plasma samples with high cardiac troponin levels induced significantly higher rates of cardiomyocyte apoptosis in cell culture assays.…”
Section: Aamentioning
confidence: 99%
“…Furthermore, patients with AA totalis/universalis showed the greatest systemic inflammatory tone relative to all the other patient cohorts, as shown by the greater degree of dysregulation of CV/atherosclerosis/immune/Th1/Th2 pathways and biomarkers 43 . Another study investigating the connection between atherosclerosis and AA found that when evaluating the serum concentrations of proinflammatory proteins, particularly CCL7, there was a positive correlation between the serum concentration of CCL7 and the severity of AA ( r = 0.281; p = 0.03), suggesting that the severity of AA may be associated with an increased risk of atherosclerosis 55 …”
Section: Nonscarring Alopeciasmentioning
confidence: 99%
“…The cardiovascular risk was calculated with various validated cardiovascular risk scoring systems: QRESEARCH risk estimator version 3 (QRISK-3) [6] in all patients; Framingham Risk score -Coronary heart disease (FRS-CHD) [7] and Framingham Risk Score -Cardiovascular Disease (FRS-CVD) [8] in patients at the age of 30 or above; Atherosclerotic Cardiovascular Disease (ASCVD) Risk Estimator Plus [9] and Systematic Coronary Risk Evaluation (SCORE) Dane dotyczące ryzyka sercowo-naczyniowego u osób z łysieniem plackowatym są jednak ograniczone [3].…”
Section: Cardiovascular Risk Assessmentmentioning
confidence: 99%
“…To date, there have been limited data considering the cardiovascular risk in patients with alopecia areata [3]. streszczenie Wprowadzenie: Z licznych badań wynika, że łysienie plackowate wiąże się z układowym stanem zapalnym z podwyższonym stężeniem cytokin prozapalnych w surowicy.…”
unclassified